Review Article on Sarvang Abhyang and Swedan - Sharma, Siddharth; Vedpathak, Surendra; kumar, Vipin; Patidar, Anil (International Research Journal of Ayurveda & Yoga, 2022)
Ayurveda literally translates to "life science." According to Ayurveda, health does not just refer to the absence of sickness; it also refers to a person’s intellect, sense organs, and spirit being in a perfect state of harmony to bestow happiness while the body is free of disease. Abhyanga is an Ayurvedic therapy that entails massaging the entire body with a Dosha-specific warm herb-infused oil from head to toe. For specific illnesses, the oil is frequently pre-mixed with herbs. Swedana is a popular technique in Ayurvedic Panchakarma centres. Sarvanga Swedana, or passive body heat therapy, is known to generate systemic hemodynamic alterations. Swedana is typically performed after Abhyanga and/or Snehana (the administration of therapeutic oils and ghee in metered quantities for oral consumption as a pre treatment technique for cleansing therapies such as Vamana – Therapeutic vomiting and Virechana – Therapeutic purgation). Swedana causes the body to sweat, making us feel lighter and more energised. It also causes the cells to activate and wash out pollutants. We feel lighter and more at peace when our cellular metabolism improves. The paper explains the concepts of Sarvang Abhyang and Swedan in broad terms.